First measurements of field metabolic rate in wild juvenile fishes show strong thermal sensitivity but variations between sympatric ecotypes. Issue 2 (2nd December 2020) - Chung, Ming‐Tsung; Jørgensen, Kris‐Emil Mose; Trueman, Clive N.; Knutsen, Halvor; Jorde, Per Erik; Grønkjær, Peter
Abstract : The relationship between physiology and temperature has a large influence on population‐level responses to climate change. In natural settings, direct thermal effects on metabolism may be exaggerated or offset by behavioural responses influencing individual energy balance. Drawing on a newly developed proxy, we provide the first estimates of the thermal performance curve of field metabolism in a wild fish. We investigate the thermal sensitivity of field metabolic rate in two sympatric, genetically distinct ecotypes of Atlantic cod from the Skagerrak coast of southern Norway. The combined ecotype median of field metabolic rate increased with increasing temperature until around 16°C, coincident with the thermal optimum for growth for juvenile Atlantic cod. Individual cod experienced temperatures in excess of the thermal optimum for field metabolic rate, indicating some degree of thermal limitation of field metabolism in a complex natural environment with the potential for thermal refugia. The two cod ecotypes showed different thermal performance curves for field metabolic rate, revealing that genetic components to temperature sensitivity persist beyond acclimation effects. The cold‐adapted fjord ecotype maintained higher field metabolic rates at cooler temperatures than the warm‐adapted North Sea ecotype, which showed clear preference for warmer waters around the thermal optimum. Field metabolic rates of the two ecotypes were strongly influenced by year and location of sampling, implying more complex behavioural responses to environmental conditions. We emphasise that the energy uses reflecting physiological conditions in the field should be considered in the evaluation of the effect of climatic variables on fish population dynamics and demonstrate that otolith isotopes provide an analytical framework to answer this question.